Mass Gatherings and Public Health: Case Studies from the Hajj to Mecca - Juma Rahman (Ubiquity Press, 2017)
Background: Many new and challenging risks can be introduced during mass gatherings. The Hajj, as one of the largest mass gatherings, provides an excellent annual opportunity to reflect on the public health risk posed by international and multicultural crowds and the value of mitigation strategies. Objectives: To identify the gap between preparation and training taken before being exposed to the mass gathering and postexposure experiences, and the breach between the expectations and reality of the holy place. Methods: This was a qualitative study with in-depth interviews using semistructured questionnaires among Hajjis from 4 different countries (Bangladesh, Pakistan, Myanmar, and New Zealand). Purposive sampling was done. The present study was also supported by literature review. Findings: Findings pointed to weaknesses in implementation and enforcement of law, for both the custodian country and countries of origin of Hajjis. Disparities among developed and developing countries were also noticeable. Conclusions: From a global health and human security perspective, strengthening of core capacities in managing mass gatherings as well as researching risks posed by such gatherings are paramount to safeguard the public’s health. Attention of health professionals worldwide and adoption of strategic planning at custodian country and sending countries are obligatory.